Penerapan Universal Design Pada Asrama Mahasiswa Nusantara Surabaya terhadap Aksesibilitas Penghuni - Haryo Prastyo, Aloysius Yoga Soni (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2025)
Nusantara Student Dormitory is a dormitory with various supporting activities, such as assembly, sports, national defense activities and other activities that have a lot of space to accommodate these activities, so that the movement of occupant circulation is quite large, therefore it is necessary to apply universal design to be able to make occupant accessibility more comfortable. The purpose of this study is to determine the accessibility conditions, space, and facilities that can support various student activities and adjust to applicable universal design regulations. This study uses a qualitative approach with the methods used are observation, survey, and visual data analysis by comparing the survey results with applicable theories and regulations. The results of this study show the application of universal architecture in accordance with the theory or principles and standards that can make occupants comfortable when doing activities, so that later the application of universal design principles in the Nusantara Student Dormitory can be improved so that it can become a comfortable place in terms of accessibility for its occupants so that it allows its occupants to carry out all existing activities.